A QUASI-EXPERIMENTAL STUDY ON THE USE OF THE BERLITZ METHOD TOWARDS THE STUDENTS' PREPOSITION MASTERY - KHOIRUL WARISI; EUSABINUS BUNAU; EKA FAJAR RAHMANI (LINGUISTICA, 2023)
This research was conducted to investigate the effect of applying the Berlitz Method on Students' Preposition Mastery to eleventh-grade students of MA Raudhatul Ulum Kubu Raya. The sample of this research was the students of grade eleventh of MA Raudhatul Ulum Kubu Raya in the academic year of 2022/2023, which consisted of two classes. The total number of students was 30, divided into 15 students for the experimental class and another 15 students for the control class. The researcher used a multiple-choice test to collect the data. The test consisted of two types, namely pre-test and post-test. The data were analyzed by using the t-test formula. To know the normality by utilizing the Chi-Square formula, homogeneity by measuring F-formula, validity and reliability by exerting Kuder Richardson Formula-20 or KR 20. The experimental class was taught by using Berlitz Method while the control class was taught using the method used by the English teacher at that school. The result of the research showed that the value of t-observed was higher than the value of t-table (293>2,16) at the level significance of Î± =Â  0,05 and the degree of freedom (df)= 13. The calculation concluded that applying Berlitz Method has a significant effect on students' preposition mastery or in other words the alternative hypothesis (Ha) was accepted.